THE IMPACT OF WORKING HOURS AND WORKLOAD ON HOTEL FOOD AND BEVERAGE STAFF’S HEALTH STATUS DURING COVID-19 PANDEMIC - Arnieyantie, A.H.; Norrina, D; Nur Alia Hanani, H; Mohamad Azli, R.; Noorliza, Z.; Hussin Khan, R.K. (International Journal of Accounting, Finance and Business, 2022)
The COVID-19 pandemic had a significant influence on several industries,particularly the hotel industry. The hotel's decision to reduce employee numbers as part of itssurvival strategy has had an impact on the surviving employees, including increased workloadand excessive working hours. As a result, this study investigated the impact of working hoursand workload on the health of hotel food and beverage workers during the COVID-19 epidemic.The quantitative approach using an online survey was applied throughout the study. The datawere analyzed using Statistical Package for the Social Sciences (SPSS) version 20 afterdelivering a questionnaire to 100 respondents. Only one of the two independent factorsevaluated has a significant (p<0.05) impact on the health of hotel food and beverage employees.Workload influences the health of hotel food and beverage employees, according to the study.Based on the findings, management should prioritize job distribution by stressing workdelegation according to the job description, job schedule, task SOP, and teamwork amongemployees to reduce workload and prevent health problems among hotel food and beverageemployees.